2019
DOI: 10.1021/acscatal.9b02783
|View full text |Cite
|
Sign up to set email alerts
|

Switching on a Nontraditional Enzymatic Base—Deprotonation by Serine in the ent-Kaurene Synthase from Bradyrhizobium japonicum

Abstract: Terpene synthases often catalyze complex carbocation cascade reactions. It has been previously shown that single-residue switches involving replacement of a key aliphatic residue with serine or threonine can "shortcircuit" such reactions that are presumed to act indirectly via dipole stabilization of intermediate carbocations. Here a similar switch was found in the structurally characterized ent-kaurene synthase from Bradyrhizobium japonicum. Application of a recently developed computational approach to terpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…While it has been suggested that the G1/2 helix break is important for the initial 1,10-ring closure, 20 these mutants do not seem to affect this first (macro)cyclization, but instead the subsequent protonation-initiated (bi)cyclization and/or rearrangement, as well as the second addition of water. Although the ability of hydroxylated amino acid side chains to serve as catalytic bases deprotonating carbocations in TPSs has been shown, 16 the effects of the T409 and S410 mutants do not seem to indicate such a role for these residues in ZmEDS either. On the other hand, it could be argued that T409 might play a role in positioning the water to be added to the eudesmolyl carbocation.…”
Section: ■ Methodscontrasting
confidence: 99%
See 4 more Smart Citations
“…While it has been suggested that the G1/2 helix break is important for the initial 1,10-ring closure, 20 these mutants do not seem to affect this first (macro)cyclization, but instead the subsequent protonation-initiated (bi)cyclization and/or rearrangement, as well as the second addition of water. Although the ability of hydroxylated amino acid side chains to serve as catalytic bases deprotonating carbocations in TPSs has been shown, 16 the effects of the T409 and S410 mutants do not seem to indicate such a role for these residues in ZmEDS either. On the other hand, it could be argued that T409 might play a role in positioning the water to be added to the eudesmolyl carbocation.…”
Section: ■ Methodscontrasting
confidence: 99%
“…The resulting complexes were visualized with PyMOL 1.8.x. A Mg 2+ –diphosphate complex was placed in ZmEDS by modeling with a distinct TEAS structure (PDB entry 4RNQ) as the template and then placing the Mg 2+ –diphosphate complex from this into the modeled ZmEDS structure, much as previously described for other TPSs …”
Section: Methodsmentioning
confidence: 55%
See 3 more Smart Citations